AVALIAÇÃO DE SISTEMAS ADESIVOS MODIFICADOS POR DIACETATO DE CLOREXIDINA - Grande, Rodrigo Stanislawczuk (2012)
The aim of this work were investigate the microtensile bond strength (μTBS), nanoleakage (NL), nano-hardness (NH) and Young’s modulus (YM) of resin-dentin bonding components produced by two simplified etch-and-rinse adhesive with different concentrations of chlorhexidine diacetate (CHX). 99.9% of CHX were added to Ambar (FGM) and XP Bond (Dentsply) in concentrations of 0, 0.01, 0.05, 0.1 and 0.2 wt%. Resin-dentin bonded sticks (0.8 mm2) were prepared for μTBS testing (0.5 mm/min). For NL, some bonded sticks from each tooth were used. Nano-indentations were made on the adhesive interface and NH and YM calculated. The results of μTBS, NL and NH and YM of the hybrid layers of the CHX-free and CHX-containing adhesives were statistically similar (p > 0.05) on immediately time. After 12 months, significant reductions of μTBS were observed for both adhesives in the control group (p< 0.05). In CHX-containing adhesives or CHX-free groups the BS remained stable for both systems. NL was more evident in the control than in the experimental groups (p < 0.05) both in IM and 12 months periods. Conclusions: CHX in concentrations lower than 0.1 wt% incorporated in the two simplified etch-and-rinse adhesives did not impair the immediate resin-dentin bond strength, nanoleakage and mechanical properties of the adhesive and hybrid layers.